The Role and Impact of Dyslexia Awareness Workshops in the Medical Curriculum - Mitchell Osei-Junior; Mayya Vorona (University Library System, University of Pittsburgh, 2022)
Background: To increase recognition of the number of students who study medicine with dyslexia and the support available, it is important to cultivate a culture in which peers can support fellow peers with dyslexia academically and pastorally. This study aims to understand medical students' perceptions of dyslexia and confidence with supporting fellow peers with dyslexia before and after a workshop on Dyslexia. Method: Pre-Post Intervention Evaluation form of 36 1st year medical students before the start of a small group dyslexia awareness session and one month after using the standardized 36-item True/False/Don't know questionnaire "A scale of knowledge and beliefs about developmental dyslexia" to elicit any significant change in knowledge about dyslexia. A standardized 6-item Likert Scale questionnaire was also administered in the same time frame to measure confidence in supporting peers with dyslexia in terms of academically, emotionally, and signposting to reasonable adjustments and further support. Results: Pre-dyslexia awareness workshop, the mean score on the knowledge and beliefs about dyslexia questionnaire was 15.22, post-intervention this improved to 24.03 (p< 0.001). Additionally, pre-intervention greater than 70% of participants reported feeling not confident in items in the confidence questionnaire associated with supporting dyslexic peers academically or signposting to reasonable adjustments and further support. This changed post-intervention with greater than 88% agreeing or strongly agreeing with these items. Conclusion: At a baseline level, medical students have less precise accuracy in knowledge and beliefs about dyslexia and are not confident in supporting dyslexic peers academically. The findings suggest that dyslexia awareness workshops in the medical curriculum have benefits in increasing knowledge about dyslexia and providing students with confidence in supporting their fellow dyslexic peers.